Evaluation of Two Dry Commercial Therapeutic Diets for the Management of Feline Chronic Gastroenteropathy - Perea, Sally C.; Marks, Stanley L.; Daristotle, Leighann; Koochaki, Patricia E.; Haydock, Richard (Frontiers in Veterinary Science, 2017)
Management of feline chronic gastroenteropathies has included intervention with both veterinary therapeutic formulas designed to manage non-specific gastrointestinal disorders and those designed with limited novel or hydrolyzed ingredients for management of food-responsive enteropathies and steroid-responsive enteropathies (inflammatory bowel disease). There have been few studies evaluating the use of dietary intervention for the management of feline chronic gastroenteropathy. This prospective, multi-center study evaluated the use of two commercially available feline veterinary therapeutic dry diets designed to manage non-specific gastrointestinal disorders in 28 cats with a history of chronic vomiting and/or diarrhea. The majority of cats enrolled in the study had a history of vomiting (n=25), with a smaller number having a history of concurrent diarrhea (n=2) or diarrhea alone (n=3). Cats were excluded if diagnostic tests identified any systemic or infectious disease that could be associated with the clinical signs of vomiting or diarrhea, and if they were panhypoproteinemic, hypoalbuminemic, hypocobalaminemic, or had a Spec fPL ≥ 5.4 μg/L. Cats were randomized to one of two veterinary therapeutic diets for four weeks. Feeding of both therapeutic diets resulted in a numeric reduction in the number of vomiting episodes over the four-week period, but no significant differences were seen between dietary interventions. When looking within dietary groups, significant differences were seen in cats fed Diet A with reductions of 69.1%, 73.3%, and 63.2% (p-values of 0.008, 0.003 and 0.029) in weeks 2, 3, and 4 respectively when compared to week 0. The probability of vomiting also showed significant reductions in cats fed Diet A between weeks 0 and 2, 3, and 4, with odds ratios of 0.008, 0.005, and 0.005 respectively (p-values of 0.038, 0.23 and 0.23). Results of this study demonstrate that a veterinary therapeutic gastrointestinal formula can be effective in the management of feline chronic vomiting. Cats that fail to respond to this dietary approach after a 2-4 week trial may benefit from a limited novel or hydrolyzed ingredient formula, and may require additional diagnostics to better characterize the underlying disease.